The Services of PT. ASDP Indonesia Ferry - Sutrisno, Slamet Prasetyo; Santoso, Santoso; Khairani, Muhammad (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
This research is motivated by the importance of a service PT. ASDP Indonesia Ferry at Penajam Port, North Penajam Paser Regency. The people's oblique view of the long crossing in line, from the time of entering the ship, the loading and unloading process and the travel time to the lack of additional infrastructure for port development. This paper aims to determine the implementation of PT. ASDP Indonesia Ferry in providing services to service users/passengers with ferry transportation services at the port of Penajam, Penajam Paser Utara Regency in accordance with Indonesian Act No. 17 of 2008, including several things, namely transportation and port services. The method used in this research is descriptive qualitative method, using data collection techniques through interviews, observation and documentation. As for the technical data analysis, the authors use an interactive model which is a series of data collection processes, data reduction, data presentation and data conclusion/verification.